ADAMTS10-mediated tissue disruption in Weill–Marchesani syndrome. (27th July 2018) - Mularczyk, Ewa J; Singh, Mukti; Godwin, Alan R F; Galli, Francessco; Humphreys, Neil; Adamson, Antony D; Mironov, Aleksandr; Cain, Stuart A; Sengle, Gerhard; Boot-Handford, Ray P; Cossu, Giulio; Kielty, Cay M; et al.
Abstract: Fibrillin microfibrils are extracellular matrix assemblies that form the template for elastic fibres, endow blood vessels, skin and other elastic tissues with extensible properties. They also regulate the bioavailability of potent growth factors of the TGF-β superfamily. A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)10 is an essential factor in fibrillin microfibril function. Mutations in fibrillin-1 or ADAMTS10 cause Weill–Marchesani syndrome (WMS) characterized by short stature, eye defects, hypermuscularity and thickened skin. Despite its importance, there is poor understanding of the role of ADAMTS10 and its function in fibrillin microfibril assembly. We have generated an ADAMTS10 WMS mouse model using Clustered Regularly Spaced Interspaced Short Palindromic Repeats and CRISPR associated protein 9 (CRISPR-Cas9) to introduce a truncation mutation seen in WMS patients. Homozygous WMS mice are smaller and have shorter long bones with perturbation to the zones of the developing growth plate and changes in cell proliferation. Furthermore, there are abnormalities in the ciliary apparatus of the eye with decreased ciliary processes and abundant fibrillin-2 microfibrils suggesting perturbation of a developmental expression switch. WMS mice have increased skeletal muscle mass and more myofibres, which is likely a consequence of an altered skeletal myogenesis. These results correlated with expression data showing down regulation of Growth differentiation factor (GDF8) and Bone Morphogenetic Protein (BMP) growth factor genes. In addition, the mitochondria in skeletal muscle are larger with irregular shape coupled with increased phospho-p38 mitogen-activated protein kinase (MAPK) suggesting muscle remodelling. Our data indicate that decreased SMAD1/5/8 and increased p38/MAPK signalling are associated with ADAMTS10-induced WMS. This model will allow further studies of the disease mechanism to facilitate the development of therapeutic interventions.